Pengaruh religiusitas terhadap minat konsumsi produk halal dengan e-commerce sebagai variabel moderasi: Studi pada mahasiswa ekonomi syariah Universitas Mulawarman - Ruqayyidah Ruqayyidah; Swadia Gandhi Mahardika (Journal of Halal Industry Studies, 2026)
This study aims to analyze the influence of religiosity on interest in consuming halal products, with e-commerce as a moderating variable, among students of the Sharia Economics Study Program at Mulawarman University. This study uses a quantitative approach with a survey method. The research sample consisted of 80 respondents selected through purposive sampling. Data analysis used Moderated Regression Analysis (MRA). The results showed that religiosity had a significant effect on interest in consuming halal products. In addition, e-commerce strengthened the influence of religiosity on interest in consuming halal products, as ease of access, halal product search features, and trust in digital platforms encouraged students to prefer halal products. Thus, it can be concluded that the combination of religious values and digital technology support is an important factor in shaping halal consumption.